MECHANICAL BEHAVIOR OF VOLCANIC ASH SOILS MIXED WITH SHREDDED TIRES - Aristizabal, Daniel; Molina, Gloria (Journal of Applied Engineering Science, 2020)
Thanks to the efforts of different public and private entities, recent years have seen a growing interest in protecting the environment and in the use of non-renewable natural resources such as tires. One of the most widely accepted ways of using non-perishable materials has been their application in the construction of civil works. This paper focuses on the assessment of test tubes made up with mixtures of fine-grained volcanic ash soiland shredded tires (SDCV-NT) to be applied as an alternative material for low cost lightweight fills, that allow the use of the greatest quantity possible of tires. The physical and mechanic properties of specimens made with mixtures of soil and shredded tires were examined, varying the location of the site of soil extraction and tire size (Gravel Size- Sand and Gravel Size). It was determined that test tubes made up of 40% medium-sized shredded tires and 60% soil, reached low dry density values, and that increasing the content of shredded tires leads to greater plasticity and less compressibility. Similarly, resistance diminishes but only up to Californian Bearing Ratio (CBR) values appropriate for use in the nucleus and foundation of an embankment. For test tubes with a maximum content of 15% of type 2 shredded tires, there appeared to be little reduction in the resistance to the mixture, as long as a compaction energy of 2700 kN-m/m3is applied.
Keywords: material mixture test; mechanical behavior; shredded tires; ash soils